Características agronômicas de cultivares de trigo e qualidade tecnológica da farinha em função do espaçamento entre linhas - Pauly, Tatiane (2013)
The objective of this study was to evaluate, in two cultivars of wheat agronomic characteristics and technological quality of flour depending on the spacing. The experimental design was a randomized block with four replications in a 4 x 2 factorial, with the first factor refers to the spacing (20 cm, 28 cm, 36 cm end 40 cm) and the second factor refers cultivars (CD 150 and BRS Tarumã). The experiment was set up in Santa Tereza do Oeste/PR in May 2011 and the crop was harvested at 126 DAE for cultivar CD 150 and 168 DAE for BRS Tarumã. The yield and grain moisture were reduced with increasing spacing 3.98% and 26.18% respectively. The hectolitre weight, the thousand grain weight, moisture of flour, ash dry basis, falling number and flour color were not affected by increasing spacing. The cultivar CD 150 showed lighter color, higher hectolitre weight, less ash and fewer drop compared to BRS Tarumã